Analysis of the Application of PSAK No. 45 Financial Reporting of Non-Profit Organizations in Achieving Transparency and Accountability at Yayasan Pemberdayaan Masyarakat Amungme dan Kamoro (YPMAK) in Mimika Regency - Tsunme, Otto; Pangerapan, Sonny; Gamaliel, Hendrik (Asian Journal of Management Analytics, 2023)
This study aims to analyze the application of PSAK No. 45 financial reporting to non-profit organizations in achieving transparency and accountability at Yayasan Pemberdayaan Masyarakat Amungme dan Kamoro (YPMAK) in Mimika Regency. The type of research used is a descriptive-qualitative approach with data collection methods through observation, interviews, and foundation documents. The research results show that YPMAK has implemented PSAK No. 45 concerning the financial reporting of non-profit organizations in terms of format and structure in the preparation of financial reports. However, it does not fully implement PSAK No. 45, where YPMAK does not record funding activities in the cash flow statement and does not explain restrictions on donor resources. Meanwhile, transparency in the use of funds and accountability in YPMAK's financial reports have been transparent and accountable both in the presentation and submission of financial reports, so that the foundation has carried out financial reporting in a transparent and accountable manner according to the principles of professional financial management.